Pemetaan Sebaran Tempat Pembuangan Sampah (TPS) Ilegal Di Wilayah Pengembangan I Kota Pekanbaru - Medio Novindra Putra Bayu; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pekanbaru City as one of the metropolitan cities with a population of 1,064,566 people can produce 450,000 kg of daily waste in 2016 to be processed at the Muara Fajar TPA. The Development Area (WP) I which consists of Limapuluh, Senapelan, Sail, Sukajadi Districts, Pekanbaru City and has a total population of 175,666 inhabitants with a total area of 19.97 Km2. The high population and waste generated needs to be balanced with an adequate waste management system to avoid the formation of Illegal TPS. The purpose of this study is to map and measure TPS volumes and to analyze geophysical, anthropogenic and community characteristics by distributing questionnaires and conducting interviews. This research was conducted by conducting a direct visit to the study area with the help of the Garmin 60CSx GPS, the results of the review were then mapped with the ArcMap 10.3 application. The results of the field survey were obtained as many as 16 illegal TPS points in WP I with a total garbage volume measured of 58,514 m3. The existence factor of the river does not affect the emergence of Illegal TPS. For the type of land, it was concluded that vacant land is the most potential place for Illegal TPS, for the most potent type of road is the type of local road, the level of education and knowledge will influence attitudes and behavior of waste management, because the low level of education and lack of knowledge will increase attitudes and unhealthy behavior. The number of illegal dumping increases with the increasing number of respondents with other types of work or unemployment.Keyword: Geographic Information System (GIS) Illegal Dumping, ArcMAP, Mapping Ilegall Dumping